{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

ch04.1-systems-of-equations-comparative-statics

# ch04.1-systems-of-equations-comparative-statics - G = G 1...

This preview shows pages 1–8. Sign up to view the full content.

Systems of Equations and Comparative Statics Professor Erkut Ozbay Economics 300

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Systems of equations Model many participants Model many markets Model many related variables Solving systems of equations Comparative statics Find impact of change in exogenous variable on endogenous variables
Supply and demand 2 4 6 8 1 0 2 10 S D S D Q P Q P Q Q = - = - = Q P 2 10 2 12 6 4 S D P P P P Q Q - = - = = = =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Supply and Demand Demand equation Q D = a – bP + cG G = price of substitute good a, b, c > 0 are parameters Supply equation Q S = d + eP Balance equation Q D = Q S = Q Substitute into balance equation d + eP = a – bP + cG Solve for P (b + e)P = a – d +cG P = (a – d +cG)/(b+e) Plug P into Q S or Q D Q = d + e(a – d +cG)/(b+e)
Comparative statics: Increase in price of substitute, G P P 1 P 0 Q Q 0 S D 0 D 1 P Q D = a – bP + cG Q S = d + eP c G Q 1 Q

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Comparative statics How does change in exogenous variable G impact endogenous variables P and Q? P = (a – d +cG)/(b+e) Q = d + e(a – d +cG)/(b+e) 2200 ∆

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: G = G 1 – G ; ∆ P = P 1 – P ; ∆ Q = Q 1 – Q • P 1 = (a – d +cG 1 )/(b+e) P = (a – d +cG )/(b+e) 2200 ∆ P = ∆ G c/(b + e) • Q 1 = d + e(a – d +cG 1 )/(b+e) Q = d + e(a – d +cG )/(b+e) 2200 ∆ Q = ∆ G ec/(b + e) Exercise: Solve for x, y, z • x = 6z + 3h – 4a + 10 • y = 4z – h + 6 • x = y • Substitute 1 st and 2 nd into 3 rd 6z + 3h – 4a + 10 = 4z – h + 6 • Solve for z 2z = 4a – 4h – 4 ⇒ z = 2a – 2h – 2 • Substitute z into 1 st and 2 nd x = 12a – 12h – 12 + 3h – 4a + 10 = 8a – 9h – 2 y = 8a – 8h – 8 – h + 6 = 8a – 9h – 2 Exercise: Impact of ∆ h = 3 • x = 8a – 9h – 2 • y = 8a – 9h – 2 • z = 2a – 2h – 2 2200 ∆ x = – 9 ∆ h = – 27 2200 ∆ y = – 9 ∆ h = – 27 2200 ∆ z = – 2 ∆ h = – 6...
View Full Document

{[ snackBarMessage ]}